THE 2005 PRESIDENTIAL ELECTION IN KAZAKHSTAN: PROBLEMS AND PROSPECTS FOR POLITICAL LIBERALIZATION - SHAYMERGENOV, Timur (CENTRAL ASIA AND THE CAUCASUS, 2006)
In recent years, the world’s attention has been riveted on the fairly inordinate political trends in some of the post-Soviet states. The Color Revolutions in Georgia, Ukraine, and Kyrgyzstan surprise no one; experts are talking about their recurring nature against the background of elections, similar plots, the technologies used to launch the sociopolitical developments, and similar results. This has created the fashionable habit of discussing every CIS country getting ready for another round of elections as a testing ground for another “color” syndrome of its political democratization. As soon as this fashion reached Central Asia, Kazakhstan became the target of expert speculation: would the republic, due to hold its next presidential election in 2005-2006 (it took place on 4 December, 2005), experience a Color Revolution? The country’s geographic proximity to Kyrgyzstan, where democratization has been very painful, and Uzbekistan, where the authorities promptly suppressed a similar attempt, stirred up interest in Kazakhstan even more. Kazakhstan’s geopolitical situation can be described as strategically very advantageous and very complicated at one and the same time. On the one hand, the republic is part of a very contradictory region prone to destabilization; and on the other, the state’s geostrategic and geo-economic potential is high enough to attract the attention of the leading global players—Russia, China, the United States, and the European Union as a whole, along with its individual countries. This largely determines the republic’s behavior on the international scene. Today, the geopolitical situation in Central Asia and across the post-Soviet space has created a potentially explosive environment. For this reason, the election period could potentially trigger any domestic political scenario. Experts could not agree on the possibility of a Color Revolution in Kazakhstan. Time has demonstrated that none of the scenarios tried out elsewhere could be applied here. The country does not belong to the classical group of post-Soviet states—its political and socioeconomic specifics set it apart from other states Astana has set itself the long-term aim of becoming an open democratic society. In the context of the fairly complex international situation and security threats, this ambitious aim is hard to realize. The well-substantiated strategy and flexibility of the republic’s leaders allow the country to consistently resolve its tasks. It is going on with its political modernization, the progress of which affects all spheres of the state’s functioning. This is amply testified not only by numerous commentaries by foreign politicians, but also by the country’s high level of investment attractiveness and its high economic development rates. Thanks to its achievements in the sphere of political liberalization and democratization, the republic is candidate No. 1 for OSCE chairmanship in 2009, since the international community has already positively assessed the republic’s chances of building an open democratic society.